2008
DOI: 10.1208/s12249-007-9025-5
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of PEGylated Derivatives of Rosin as Sustained Release Film Formers

Abstract: Abstract. The purpose of the present study was to investigate the potential use of two PEGylated derivatives of rosin (PD) as sustained release film forming materials. The derivatives differed chemically by their acid numbers-PD-1 with 120.93 and PD-2 with 88.19. The derivative films were characterized for surface morphology, water uptake-weight loss, angle of contact, water vapor transmission rate, mechanical properties and permeability study. Dissolution of diclofenac sodium (DS) and propranolol hydrochlorid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
(23 reference statements)
0
8
0
Order By: Relevance
“…43 These rosin microparticulate drug delivery systems provide opportunity not only to be used for controlled drug delivery but also the drug release can be prolonged by increasing the circulation time through PEGylation of rosin microparticles. 44,45 Morkhade et al 46 prepared PEGylated rosin derivatives successfully investigated for their drug loading and release potentials using diclofenac and diltiazem as model drug. PEGylation of rosin and its derivatives can be used to improve the in vivo performance of numerous therapeutic substances such as proteins, peptides and some drug delivery devices such as nanoparticles and microparticles.…”
Section: Pharmaceutical Applications Of Rosinmentioning
confidence: 99%
“…43 These rosin microparticulate drug delivery systems provide opportunity not only to be used for controlled drug delivery but also the drug release can be prolonged by increasing the circulation time through PEGylation of rosin microparticles. 44,45 Morkhade et al 46 prepared PEGylated rosin derivatives successfully investigated for their drug loading and release potentials using diclofenac and diltiazem as model drug. PEGylation of rosin and its derivatives can be used to improve the in vivo performance of numerous therapeutic substances such as proteins, peptides and some drug delivery devices such as nanoparticles and microparticles.…”
Section: Pharmaceutical Applications Of Rosinmentioning
confidence: 99%
“…PRDs could be used successfully to prepare matrix tablets, coated pellets, and microparticles for sustained drug release. 4,911…”
Section: Introductionmentioning
confidence: 99%
“…PRDs could be used successfully to prepare matrix tablets, coated pellets, and microparticles for sustained drug release. 4,[9][10][11] Simultaneously, with the evaluation of rosin and its polyhydric alcohol-based derivatives for drug delivery applications, attempts were also made to assess their biodegradation and biocompatibility. [12][13][14][15] It was found that the biodegradation and biocompatibility of native rosin and its polyhydric alcohol-based derivatives were comparable to that of poly(d,l-lactide-co-glycolide) (PLGA).…”
Section: Introductionmentioning
confidence: 99%
“…They are monocarboxylic acids of alkylated hydrophenanthrene; abietic acid constitutes the principal resin acid. [3], [4]. It is soluble in alcohol, ether, benzene and chloroform but insoluble in water Polyethylene glycol (PEG) or poly (ethylene oxide) is petroleum base polymer represent water-soluble mono hydroxy alcohols.…”
Section: Introductionmentioning
confidence: 99%